Relation between hyponatremia and alteration in gross metabolic parameters after atypical antipsychotic therapy - Daryani, K. K.; Sethi, Gargi; Sethi, Shivank (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Weight gain and hyponatremia which is dilutional in nature, has been well known adverse effects associated with use of atypical antipsychotic medication but the plausible impact of dilutional hyponatremia on weight gain has not been explored. Methods: One hundred and three patients more than 18 years of age of either gender who were prescribed, olanzapine or risperidone, were tested for serum electrolytes (Na+ and K+) and gross metabolic parameters (weight and waist circumference) were measured for baseline and post drug testing. Results: Most common age group was 30-39 years of age in the patient study sample (n=103) with 38 (36.90%) patients were females while rest 63 (63.10%) were males. There was no significant association between serum sodium levels and weight gain was observed (p >0.05). It was observed that in olanzapine group 64% of the studied cases had weight gain whereas in risperidone group only 20.8% reported weight gain (p <0.001). There was significant association between olanzapine and increase in waist circumference over risperidone, irrespective to serum sodium status (x2=0.0148, p >0.05). Conclusions: Olanzapine was primarily responsible for weight gain and increase in waist circumference over risperidone. These gross metabolic parameters were not influenced by hyponatremia.